2011
DOI: 10.1109/tasc.2011.2144979
|View full text |Cite
|
Sign up to set email alerts
|

Induction Heating of Aluminum Billets With Linear Motion in a Strong DC Magnetic Field: Magnetothermal Analysis in Two-Dimensional

Abstract: This paper presents a new structure of an induction heater for aluminium billets. The device consists in using a strong DC magnetic field created by a superconducting inductor in which the conducting billet is actuated by a linear motion at a constant velocity. The analysis, based on the analytical model for the magnetic field in the billet, has been developed, and then the eddy currents and induced heating power have been evaluated. The analytical results are compared to those issued from a finite element sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Analytical methods are more suitable for the integral parameters calculation and analysis. Also, this method is more convenient for simple geometries calculations and some assumptions or sometimes reduction of dimension may be essential [2, 6]. Whereas, the finite‐element methods (FEMs) are more universal and it's very useful for analysing the induced eddy currents and power distribution if a high accuracy is demand, such as consideration of the both edge‐effects and slots effects of the induction end workpiece.…”
Section: System Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical methods are more suitable for the integral parameters calculation and analysis. Also, this method is more convenient for simple geometries calculations and some assumptions or sometimes reduction of dimension may be essential [2, 6]. Whereas, the finite‐element methods (FEMs) are more universal and it's very useful for analysing the induced eddy currents and power distribution if a high accuracy is demand, such as consideration of the both edge‐effects and slots effects of the induction end workpiece.…”
Section: System Analysismentioning
confidence: 99%
“…These features may be achieved in the best manner by the so‐called travelling wave induction heating, which has concerned from many industrial applications in the field of heating flat materials [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…For the same reason, salient poles and non‐uniform air‐gap, some of the magnetic flux lines leak out the yoke and diverge out the area faces of the heater, which causes unfocused induced eddy current and reduces heat generation; this is the second drawback of the TW inductor. Those could affect the power is to be transferred efficiently from the coil to the load [6].…”
Section: Slot Effectsmentioning
confidence: 99%
“…However, the subsequent efficiency analysis indicated that the overall energy efficiency of this HTS AC induction heater for nonmagnetic metal billets does not exceed 60% and need to be faced with new problems because it is still unavoidable for HTS windings to suffer serious AC losses and the resulting quench of HTS coils from Joule heat. In addition, the problem of low heating depth along radical direction caused by skin effect is also unavoidable in electromagnetic induction heating process [9]- [11]. Reduce the frequency of alternating current (even as low as 3 -7 Hz) to obtain large heat penetration depths may be a solution, but it is difficult to achieve under the premise of high heating efficiency.…”
Section: Introductionmentioning
confidence: 99%